Housing-related challenges during COVID-19 pandemic among urban poor in low- and middle-income countries: A systematic review and gap analysis - Dubey, Shubhankar; Sahoo, Krushna Chandra; Dash, Girish Chandra; Sahay, Mili Roopchand; Mahapatra, Pranab; Bhattacharya, Debdutta; Barrio, Mariam Otmani del; Pati, Sanghamitra (Frontiers in Public Health, 2022)
The abysmal health of the urban poor or slum dwellers was attributed to structural inequities such as inadequate housing, water, and sanitation. This review aimed to assess housing-related opportunities and challenges during the COVID-19 pandemic among urban poor in low-and middle-income countries. For study identification, a comprehensive search was performed in eleven databases that yielded 22 potential studies. The inadequate housing infrastructure makes the lives of the urban poor more precarious during COVID-19. Typically, the houses lacked lighting, ventilation, and overcrowding. This review reflected that it is crucial to reimagine housing policy for the urban poor with an emphasis on pandemic/epidemic guidelines.